2022
DOI: 10.1186/s12889-022-13479-0
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and healthcare utilization in France: evidence from the European Health Interview Survey (EHIS) 2014

Abstract: Background A growing need and focus on preventing and controlling the diseases and promoting a healthier lifestyle is more evident at global, regional, and national levels. In this respect, it is well-known the positive association between physical activity and population’s health, but also its negative association with the demand of healthcare, which could lead to lower spending on healthcare systems. In France, a lack of physical activity, a high prevalence of sedentary behaviours, and a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 90 publications
(162 reference statements)
2
6
0
5
Order By: Relevance
“…The short-term findings were supported by our longitudinal analyses, as decreased engagement and consistent nonparticipation in creative and physical activities were associated with increased length of hospital stay and (for physical activities) use of community health care. This is also in line with previous evidence on the associations of physical activity with lower levels of health care utilization in later life, which could be explained through the health benefits of physical activity, including improved physical functional abilities, facilitated disease recovery, and phycological benefits …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The short-term findings were supported by our longitudinal analyses, as decreased engagement and consistent nonparticipation in creative and physical activities were associated with increased length of hospital stay and (for physical activities) use of community health care. This is also in line with previous evidence on the associations of physical activity with lower levels of health care utilization in later life, which could be explained through the health benefits of physical activity, including improved physical functional abilities, facilitated disease recovery, and phycological benefits …”
Section: Discussionsupporting
confidence: 91%
“…This is also in line with previous evidence on the associations of physical activity with lower levels of health JAMA Network Open | Health Policy care utilization in later life, which could be explained through the health benefits of physical activity, including improved physical functional abilities, facilitated disease recovery, and phycological benefits. [45][46][47] Our results are consistent with previous theories that SCCE could reduce demand for secondary care services, 24 although they show nuance in 2 ways. First, it was length of hospital stay rather than admissions or readmissions that were associated with SCCE.…”
Section: Inpatient and Community Health Caresupporting
confidence: 90%
See 1 more Smart Citation
“…Studies [ 44 , 45 ] have also validated the reducing effect of physical activity on healthcare utilization. However, [ 46 , 47 , 48 ] noted that the association of physical and healthcare utilization is dependent on age. Similarly, regarding the co-occurrence or clustering of behavior, [ 35 ] found that participants having seven unhealthy lifestyles are 24 percent less likely to visit a GP for medical consultation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies have used total or mean values for intensity or duration of a physical activity. In addition, these were subjective and often focused on an activity domain of interests, including leisure time, household, transportation, and work [2,4,5]. Therefore, objective and comprehensive information about habitual physical activity in daily life has not been accurate enough because of overly compressed and subjective information prone to memory bias [6].…”
Section: Introductionmentioning
confidence: 99%